Perioperative Intravascular Fluid Assessment and Monitoring: A Narrative Review of Established and Emerging Techniques - Sumit Singh; Ware G. Kuschner; Geoffrey Lighthall (Anesthesiology Research and Practice)
Accurate assessments of intravascular fluid status are an essential part of perioperative care and necessary in the management of the hemodynamically unstable patient. Goal-directed fluid management can facilitate resuscitation of the hypovolemic patient, reduce the risk of fluid overload, reduce the risk of the injudicious use of vasopressors and inotropes, and improve clinical outcomes. In this paper, we discuss the strengths and limitations of a spectrum of noninvasive and invasive techniques for assessing and monitoring intravascular volume status and fluid responsiveness in the perioperative and critically ill patient.